2001
DOI: 10.3109/10253890109014754
|View full text |Cite
|
Sign up to set email alerts
|

Metyrapone Reveals That Previous Chronic Stress Differentially Impairs Hippocampal-dependent Memory

Abstract: Chronic stress facilitates fear conditioning in rats with hippocampal neuronal atrophy and in rats in which the atrophy is prevented with tianeptine, a serotonin re-uptake enhancer. The purpose of this study was to determine whether the lack of dissociation between fear conditioning performance and hippocampal integrity was masked by the presence of endogenous corticosteroids during training. As in previous studies, rats were stressed by daily restraint (6 h/day for 21 days), trained in the conditioning chambe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 62 publications
1
25
0
1
Order By: Relevance
“…Body weight gain was analyzed because previous studies have shown that chronic stress reduces weight gain in male rats (Conrad et al 2001, Magariños and McEwen 1995, Watanabe et al 1992. A 2 ×4 repeated measures ANOVA for stress treatment (control & stress) and day (1, 7, 14 & 21) revealed a significant main effect for stress, F(1, 32) = 35.49, p < 0.001, a significant main effect for day, F(3, 96) = 746.86, p < 0.001, and a significant interaction between stress and day, F(3, 96) = 141.20, p < 0.001, showing that stressed rats gained weight more slowly than controls over three weeks of restraint (Control d1 329.6 ± 4.29, d21 449.2 ± 5.49; Stress d1 342.6 ± 3.29, d21 385.5 ± 3.5).…”
Section: Resultsmentioning
confidence: 99%
“…Body weight gain was analyzed because previous studies have shown that chronic stress reduces weight gain in male rats (Conrad et al 2001, Magariños and McEwen 1995, Watanabe et al 1992. A 2 ×4 repeated measures ANOVA for stress treatment (control & stress) and day (1, 7, 14 & 21) revealed a significant main effect for stress, F(1, 32) = 35.49, p < 0.001, a significant main effect for day, F(3, 96) = 746.86, p < 0.001, and a significant interaction between stress and day, F(3, 96) = 141.20, p < 0.001, showing that stressed rats gained weight more slowly than controls over three weeks of restraint (Control d1 329.6 ± 4.29, d21 449.2 ± 5.49; Stress d1 342.6 ± 3.29, d21 385.5 ± 3.5).…”
Section: Resultsmentioning
confidence: 99%
“…The amygdala is necessary for acquisition of fear conditioning [22,248], which is enhanced by chronic stress in males [23,249] or GC [24]. Similarly, chronic stress enhances dendritic arborization in the amygdala of males [117,123,250], a mechanism that may contribute to enhanced acquisition of fear conditioning.…”
Section: Sex-specific Chronic Stress Effects On Pfc and Amygdala Morpmentioning
confidence: 99%
“…Although CA3 dendritic retraction is associated with memory deficits in males, chronically-stressed male rats exhibit increased hippocampal-dependent contextual fear conditioning compared with controls, despite CA3 dendritic retraction (Conrad et al, 1999(Conrad et al, , 2001). In addition, inhibiting CORT synthesis with metyrapone on the day of training prevents stress-induced spatial memory deficits when dendritic retraction should be present (Wright et al, 2004).…”
Section: Significancementioning
confidence: 99%